Integrasi Model Polya dalam LKPD Interaktif Menggunakan Liveworksheets untuk Meningkatkan Kemampuan Eksplorasi Ide Siswa Sekolah Dasar dalam Penyelesaian Soal Cerita Matematika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Mathematical disposition as affective mathematics has an important role for student character especially in society environment. One of indicator of mathematical disposition is the ability to explore ideas. However, based on a preliminary study through interview, observation and documentation of fifth grade math learning at MI Al-Islah, Berbek, shows that the ability to explore ideas in solving fractional story problems is still low, namely 70% of students have not been able to translate story questions into mathematical sentences. Whereas the ability to explore ideas is important for students as a form of differentiation of ideas. By Integrating the Polya Model into the Interactive Student Worksheet (LKPD) is an appropriate guideline to guide students in solving math story problems. Interactive LKPD is developed through Live Worksheets using steps to solve mathematical problems by the Polya Model. The results showed that after the experiment and implementation of the developed teaching materials, the students ability to explore ideas increased to 60%. With an indication that students are able to make mathematical sentences well, the methods used by students are also varied with the same result and students are more enthusiastic to participate in learning.
Keywords: Exploration of ideas; Interactive Student Worksheet; Polya Model